The Effect Of Work Facilities And Compensation On Employee Performance At PT. Rentang Buana Niagamakmur Tasikmalaya Branch - Rachmasari, Riva Tri; Karmila, Mila; Sutrisna, Arga (Universitas Dehasen Bengkulu, 2023)
The purpose of this study is to determine the effect of work facilities and compensation on employee performance at PT. Rentang Buana Niagamakmur, Tasikmalaya Branch. The research method used is a quantitative method of 80 respondents who are employees of PT. Rentang Buana Niagamakmur, Tasikmalaya Branch. The types of data used are primary data and secondary data. The data analysis technique used is multiple regression analysis. The results of this test prove that work facilities and compensation have a significant effect both partially and simultaneously on the work performance of employees of PT. Rentang Buana Niagamakmur, Tasikmalaya Branch.